A literature review on the role of Culicoides in the transmission of avian blood parasites in Europe - Carolina Romeiro Fernandes Chagas; Rasa Bernotienė; Aneliya Bobeva; Dovilė Bukauskaitė; Martina Ferraguti; Rafael Gutiérrez-Lopez; Margarita Kazak; Bruno Mathieu; Kristina Valavičiūte-Pocienė; Diego Santiago-Alarcon; Milena Svobodová; Jesús Veiga; et al. (Parasites & Vectors)
Abstract Culicoides (Diptera: Ceratopogonidae) biting midges are a diverse group of insect vectors that transmit pathogens affecting humans, livestock, and wild animals. Among them, Oropouche virus, African Horse sickness virus, and bluetongue virus are the most notable pathogens. However, comparatively little is known about which Culicoides species serve as vectors of wildlife parasites affecting wild birds globally, including the malaria-like parasite of the genus Haemoproteus (Haemosporida: Haemoproteidae) and kinetoplastid Trypanosoma (Trypanosomatida: Trypanosomatidae). Beyond the direct impact of their bites, infections by these parasites negatively affect wild birds from early developmental stages, significantly influencing their ecology and evolution. Here, we present a comprehensive review of the role of Culicoides species in the transmission of these two genera of avian parasites in Europe: Haemoproteus and Trypanosoma. We identify key information and methods used to study Culicoides–bird–parasite interactions, from insect sampling to vector competence assessment. Additionally, we highlight key knowledge gaps and propose future research directions in this area. Graphical Abstract